Reading risk: Preparing students to develop critical digital literacies and advocate for privacy in digital spaces - Reilly, Colleen A. (Computers and composition, 2021)
•Privacy risks online are obscured by surveillance capitalists’ obfuscation.•Models of privacy do not account for users’ inability to protect their data.•Students can viscerally experience online surveillance through targeted assignments.•Shifting from privacy awareness to suspicion spurs advocacy for legal protections.•Statutes like GDPR and CCPA can improve citizens’ privacy rights and protections. Models of privacy in digital spaces place the responsibility on individuals to protect their data and prevent harm from breaches. As I demonstrate in this article, the massive collection of individuals’ data online, an inherent feature of surveillance capitalism, makes it virtually impossible for individuals to self-manage their privacy and security. In fact, corporate interests who benefit from the ubiquitous digital surveillance online purposely obscure their activities, complicating the ability of users to accurately perceive the degree of risk inherent in online activities. Our concepts of privacy and responsibility online further disempower users and dissuade them from demanding privacy as a human right. While some individually initiated protective behaviors can be efficacious in curbing localized harm, significant legal reforms are needed for lasting privacy protection and harm reduction for all users. My discussion demonstrates how, as writing teachers, we can help students to become advocates for legal and regulatory reforms through completing assignments, such as the tracking report described herein, that help them to experience and, thus, more accurately read the risks resulting from compromised privacy in digital spaces.